Agreement between the Takeda UA-731 automatic blood pressure measuring device and the manual mercury sphygmomanometer: an assessment under field conditions in Newcastle upon Tyne, UK. Issue 2 (April 1996) - Cartwright, C; Unwin, N; Stephenson, P
Abstract : STUDY OBJECTIVE: To assess agreement between two Takeda UA-731 automatic blood pressure measuring devices (referred to as machines A and B) and two manual mercury sphygmomanometers. DESIGN: A 'Y' connector attached each Takeda UA-731 to a manual mercury sphygmomanometer. Simultaneous measurements were made on adult subjects. SETTING: A population based cardiovascular disease survey in Newcastle upon Tyne, UK. PARTICIPANTS: Measurements on machine A were compared in 71 individuals (all women), and on machine B in 75 individuals (9 men, 66 women). The age range of subjects was 28 to 76 years and median ages were 59 years for machine A and 50 years for machine B. MAIN RESULTS: Blood pressure (mmHg) ranged from 72 to 212 systolic and 44 to 102 diastolic. Both Takedas gave significantly lower readings than the manual devices for systolic and diastolic pressures: differences were mean (SD: 95% CI) 3.7 mmHg (6.5: 2.2, 5.2) for machine A systolic, 2.3 mmHg (4.5: 1.3, 3.4) machine A diastolic; 1.8 mmHg (6.2: 0.4, 3.3) machine B systolic, and 1.8 (4.4: 0.8, 2.8) machine B diastolic. On the British Hypertension Society criteria, machine A was graded C on systolic measurements and B on diastolic; machine B was graded B on both systolic and diastolic measurements. CONCLUSIONS: The performance of these machines compares favourably with the Dinamap 8100, recently adopted for survey work by the Department of Health. The Takeda UA-731 looks promising for epidemiological survey work but before it can be fully recommended further evaluations are needed.